Effect of Omega-3 on lipid profile in type 2 diabetic patients - Abdulellah Fadhil, Omer; B. Al-Youzbaki, Wahda (Tikrit Journal of Pharmaceutical Sciences, 2023)
Diabetic complication is a major health concern , especially uncontrolled lipid profile, contributing to cardiac, renal and multisystem disorders. To evaluate the effect of 2 months supplementation of Omega-3 on lipid profile in type 2 diabetic patients and in comparison with the control. This non-randomized clinical trial was conducted at Al-Wafa'a Center for Diabetes Management and Research in Mosul City in the period from 1st of February 2012 to the 1st of July 2012. A total number of 84 patients (42 males and 42 females) diagnosed with type 2 diabetes mellitus (T2DM) for 2-5 years and were treated with metformin (dose of 500 mg twice daily) + glibenclamide (dose of 2.5 mg once daily) with no other liver or renal disorders, the patients were divided into two groups: First group included 50 patients with age ranged from 37 to 61 years, the patients were given Omega-3 capsules (1000 mg twice daily) for two months (Omega-3 group). The second group included the remaining 34 diagnosed diabetic patients, matched with the first group by age, sex , and BMI and considered as (control group). Fasting blood samples were taken from the first group at the beginning then after two months of Omega-3 use and from the control group once. The sera obtained from all participants in this study were used to measure lipid profile parameters by using the commercial kits, serum low-density lipoprotein cholesterol (LDL-c) was calculated using Friedewald equation. Atherogenic index (AI) was recognized by simple equation and BMI measured by dividing weight in (kg) by square of height in (meter). There was a significant reduction of serum triglycarides (TG) level and atherogenic index but no significant changes in total cholesterol (TC), high density lipoprotein-cholesterol HDL-c, nor in LDL-c level after 2 months therapy with Omega-3 and in comparison with the control group. The use of Omega-3 supplementation for two months in type 2 diabetic patients resulted in significant reduction in the serum TG level and atherogenic index but there was no effect on the other lipid profile parameters. This may be of therapeutic importance in lowering of the cardiovascular risk factors in patients with T2DM.